2012
DOI: 10.1557/opl.2012.736
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Synthesis of Iron Core/Iron Oxide Shell Magnetic Nanoparticles and Their Physicochemical Properties

Abstract: Iron magnetic nanoparticles were synthesized under an inert atmosphere via the reaction between FeCl3 and NaBH4 in droplets of water in a microemulsion consisting of octane with cetyl trimethylammonium bromide and butanol as surfactants. A thin Fe3O4 layer was produced on the iron nanoparticles using slow, controlled oxidation at room temperature. A silica shell was deposited on the Fe3O4 using 3-aminopropyltrimethoxysilane following the method of Zhang et al. [Mater. Sci. Eng. C 30 (2010) 92–97]. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…8 A key characteristic of MNPs used for clinical hyperthermia is a high specific absorption rate (SAR), which depends on the MNPs' size, shape, composition, magnetic interaction, and concentration, as well as the applied magnetic field frequency and strength. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] There are a number of types of MNPs available for hyperthermia therapy. [12][13][14]17,28,29 However, most existing MNPs require a high frequency or high AMF strength to deliver an adequate thermal dose to the tumor.…”
mentioning
confidence: 99%
“…8 A key characteristic of MNPs used for clinical hyperthermia is a high specific absorption rate (SAR), which depends on the MNPs' size, shape, composition, magnetic interaction, and concentration, as well as the applied magnetic field frequency and strength. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] There are a number of types of MNPs available for hyperthermia therapy. [12][13][14]17,28,29 However, most existing MNPs require a high frequency or high AMF strength to deliver an adequate thermal dose to the tumor.…”
mentioning
confidence: 99%
“…The selected literature was classified into four main groups:Methods of synthesis of IONPs [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]Characterization of IONPs [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,…”
Section: Resultsmentioning
confidence: 99%
“…Methods of synthesis of IONPs [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naked metallic nanoparticles are chemically active and easily oxidized in air, which results in loss of magnetism and dispersibility . For example, it was shown that 8–16 nm Fe/Fe oxide core–shell particles show extraordinary saturation magnetization compared to other MNPs, but oxidize rapidly in water and especially in saline solution . Nanoparticles of Co or Co ferrites could be a good alternative to iron MNPs since they show better chemical stability in aquatic solutions.…”
Section: Design and Synthesis Of Mnpsmentioning
confidence: 99%